Human Capital Development in the Digital Globalization Era: Strategies for Competence, Innovation, and Organizational Competitiveness - Deswita Sari; Naila Herwina; Septiana Pasaribu; Sri Rahma Zalia; Marnis Marnis (Review: Journal of Multidisciplinary in Social Sciences, 2026)
Due to growth technology, digitalization, and global competition, the era of globalization bring change big in the business world. Source Power intelligent, flexible and creative human beings is asset strategic needs​ company Because condition This is the purpose of the research This is For analyzing human capital development strategies in the era of globalization. To reach objective this research​ This use approach qualitative descriptive in collection literature. Data from 2021–2025 collected​ from journal scientific national and international. Research results show that training and education, management talent, improvement digital competencies, and upskilling and reskilling programs are all method For developing human capital. Leadership adaptive and digital transformation of HR improves Power competition company. Therefore that, so that the organization capable face challenge globalization, approach human resource development must be implemented in a way sustainable.